If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(7v + -6) + 5v = 9 + 3(3v + -1) Reorder the terms: -2(-6 + 7v) + 5v = 9 + 3(3v + -1) (-6 * -2 + 7v * -2) + 5v = 9 + 3(3v + -1) (12 + -14v) + 5v = 9 + 3(3v + -1) Combine like terms: -14v + 5v = -9v 12 + -9v = 9 + 3(3v + -1) Reorder the terms: 12 + -9v = 9 + 3(-1 + 3v) 12 + -9v = 9 + (-1 * 3 + 3v * 3) 12 + -9v = 9 + (-3 + 9v) Combine like terms: 9 + -3 = 6 12 + -9v = 6 + 9v Solving 12 + -9v = 6 + 9v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-9v' to each side of the equation. 12 + -9v + -9v = 6 + 9v + -9v Combine like terms: -9v + -9v = -18v 12 + -18v = 6 + 9v + -9v Combine like terms: 9v + -9v = 0 12 + -18v = 6 + 0 12 + -18v = 6 Add '-12' to each side of the equation. 12 + -12 + -18v = 6 + -12 Combine like terms: 12 + -12 = 0 0 + -18v = 6 + -12 -18v = 6 + -12 Combine like terms: 6 + -12 = -6 -18v = -6 Divide each side by '-18'. v = 0.3333333333 Simplifying v = 0.3333333333
| 14.95+0.13x=60 | | k^2-3k-10=50 | | 6(u+2)=-3(3u-5)+9u | | -6(-4x+3)-9x=7(x-3)-3 | | -100=12t+4 | | (4m^2/3m^7n^3)^2 | | x^4-9/4x^2+1/2=0 | | 8x^2-18x+2=0 | | 75x=600 | | (a+3b)(3a-b)=0 | | 9/10=x/14 | | (a+3b)(3a-6b)=0 | | 1/2/3=x/12 | | 14/9/7/27 | | (15a+13b)(5a-6b)=0 | | (y/4)^-3 | | x-3.7=3.3 | | 15x^2+13xy-6y^2=0 | | 48x^2-26xy-35y^2=0 | | 48x^2-26xy-25y^2=0 | | 48x^2-26xy-25y=0 | | 50+1.75x=39.99 | | 4(p+5)=6(p-7) | | 26x^2-11x-25=0 | | 23x-5=5 | | 5.8=2.3x+1.2 | | 4+1.5y=2+3y | | 4+3y/2=4/2+3y | | f(x)=24-2x | | y=-2.2+10 | | 120x=90(x+100) | | 7b+ar=r-4c |